Beban penyakit parasitik di negara berkembang: analisis komprehensif berbasis data global dan strategi intervensi berkelanjutan - Jazuli, Muhammad Sulaiman (Maliki Interdisciplinary Journal, 2026)
Parasitic diseases remain one of the most significant public health burdens in developing countries, affecting millions of people, particularly among vulnerable populations. This article presents a comprehensive analysis of the epidemiology, social and environmental determinants, and intervention strategies for major parasitic diseases, including malaria, schistosomiasis, and soil-transmitted helminthiasis. Through a systematic review of global data and regional case studies, the article explores the geographic distribution patterns, risk factors, and socioeconomic impacts of these diseases. The analysis shows that despite progress in parasitic disease control, persistent challenges related to limited access to health services, inadequate sanitation infrastructure, climate change, and drug resistance continue to hamper elimination efforts. The article recommends an integrated multi-sectoral approach, strengthening surveillance systems, improving access to clean water and sanitation, and empowering communities as key strategies for sustainably reducing the burden of parasitic diseases.